Unfavorable Prognostic Impact of HER2 2+/FISH-Negativity in Older Patients with HER2-Negative and High-Risk Breast Cancer - Wang H; Yu M; Chen M; Li H; Liu S (Breast Cancer: Targets and Therapy, 2024)
Hao Wang,1 Miao Yu,1 Meihua Chen,2 Hui Li,1 Shiwei Liu1 1Department of Breast, Sichuan Clinical Research Center for Cancer, Sichuan Cancer Hospital & Institute, Sichuan Cancer Center, Affiliated Cancer Hospital of University of Electronic Science and Technology of China, Chengdu, 610042, People’s Republic of China; 2Department of Radiation Oncology, Radiation Oncology Key Laboratory of Sichuan Province, Sichuan Clinical Research Center for Cancer, Sichuan Cancer Hospital & Institute, Sichuan Cancer Center, Affiliated Cancer Hospital of University of Electronic Science and Technology of China, Chengdu, 610042, People’s Republic of ChinaCorrespondence: Shiwei Liu, Department of Breast, Sichuan Clinical Research Center for Cancer, Sichuan Cancer Hospital & Institute, Sichuan Cancer Center, Affiliated Cancer Hospital of University of Electronic Science and Technology of China, Chengdu, 610042, People’s Republic of China, Tel/Fax +86-02885420456, Email liushiwei@scszlyy.org.cnPurpose: Human epidermal growth factor receptor 2 (HER2)-low breast cancer, consisted of carcinomas with HER2 protein 1+ or 2+ without gene amplification, has been considered a biologically heterogeneous disease. Limited research separately investigated the prognostic significance of HER2 2+ without gene amplification, and no evidence can be identified in older patients. In this dedicated cohort of older patients with HER2-negative and high-risk breast cancer, we analyzed the real-world prognosis after standard adjuvant chemotherapy, and investigated the associations of survival with HER2 2+ without gene amplification.Patients and Methods: From January 2016 to December 2021, older patients (≥ 65 years) with breast cancer were reviewed, and HER2-negative/high-risk disease receiving standard adjuvant chemotherapy was included. HER2-negativity was defined as immunohistochemistry (IHC) score 0, 1+ or 2+ without gene amplification by fluorescent in situ hybridization (FISH). Cox proportional hazards regression analyses were performed to assess the associations of HER2 2+/FISH-negativity with disease-free survival (DFS), which was estimated by the Kaplan–Meier method and compared by the Log rank test.Results: This cohort consisted of 121 consecutive older patients. With a median follow-up of 46 months, 12 patients had a DFS event. By univariate and multivariate analyses, HER2 2+/FISH-negativity was the only independent predictor for worse DFS (hazard ratio 5.56; P=0.046). Patients with HER2 2+/FISH-negativity had significantly poorer DFS compared with those with HER2 0 or 1+ (Log rank test, P=0.029). In both hormone receptor (HR)-positive (Log rank test, P=0.052) and HR-negative (Log rank test, P=0.125) subgroups, HER2 2+/FISH-negativity showed a marginally significant adverse influence on DFS.Conclusion: In older patients with HER2-negative/high-risk breast cancer undergoing standard adjuvant chemotherapy, our findings suggest that HER2 2+/FISH-negativity has an independent negative impact on prognosis.Keywords: breast cancer, older patients, HER2-low, HER2 2+, prognosis